2016
DOI: 10.1016/j.ebiom.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Branched Chain Amino Acids Cause Liver Injury in Obese/Diabetic Mice by Promoting Adipocyte Lipolysis and Inhibiting Hepatic Autophagy

Abstract: The Western meat-rich diet is both high in protein and fat. Although the hazardous effect of a high fat diet (HFD) upon liver structure and function is well recognized, whether the co-presence of high protein intake contributes to, or protects against, HF-induced hepatic injury remains unclear. Increased intake of branched chain amino acids (BCAA, essential amino acids compromising 20% of total protein intake) reduces body weight. However, elevated circulating BCAA is associated with non-alcoholic fatty liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
127
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 36 publications
5
127
1
3
Order By: Relevance
“…These results were in consistent with Hagiwara et al , who found that BCAAs significantly suppressed TGF‐β1 in HepG2 cells. In addition, BCAAs supplementation significantly upregulated the expression of proinflammatory cytokines (TNF‐α, IL‐6, and IL‐1β) in high‐fat diet maintained mice .…”
Section: Discussionmentioning
confidence: 99%
“…These results were in consistent with Hagiwara et al , who found that BCAAs significantly suppressed TGF‐β1 in HepG2 cells. In addition, BCAAs supplementation significantly upregulated the expression of proinflammatory cytokines (TNF‐α, IL‐6, and IL‐1β) in high‐fat diet maintained mice .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome has a strong correlation with selective BCAA profile disturbances, whose availability affects glucose, protein, and lipid metabolism . Zhang, et al demonstrated that BCAAs triggered abnormal lipolysis and hyperlipidemia, causing hepatic lipotoxicity. Furthermore, BCAAs directly exacerbate hepatic lipotoxicity by reducing lipogenesis and inhibiting autophagy in the hepatocyte.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient also used supplement BCAA, which increased their levels (L-leucine, L-valine, L-isoleucine). BCAA is associated with non-alcoholic fatty liver disease and injury, and it is proven that their combination with high fat diet (HFD) in experimental mice leads to increased hepatic apoptosis, and elevated circulation hepatic enzymes [18].…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic and supportive therapies were administrated with suspension of all hepatotoxic substances he had previously been using, and the patient fully recovered. The absence of prior liver disease, as well the age of the patient were certainly good prognostic factors, but the influence of hepatoprotective effect of glutamine cannot be ignored [18].…”
Section: Discussionmentioning
confidence: 99%